Optical laminate
Patent Information
- Application Number
- JP2023126903
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-02-14
AI Technical Summary
【0006】 本発明の実施形態によれば、液晶配向固化層を含み、配向基材を剥離する際の剥離不良が抑制された光学積層体を実現することができる。
Smart Images

Figure 2025022386000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical laminate. [Background technology]
[0002] In recent years, image display devices such as liquid crystal display devices and electroluminescence (EL) display devices (for example, organic EL display devices and inorganic EL display devices) have rapidly become widespread. In many image display devices, an optical laminate including a retardation film (for example, an anti-reflection film in which a polarizing plate and a retardation film are integrated) is used. In recent years, as the demand for thinner image display devices has increased, the demand for thinner optical laminates has also increased. In order to reduce the thickness of optical laminates, the retardation layer (retardation film), which contributes greatly to the thickness, has been made thinner. A representative example of a thin retardation film is a film in which a liquid crystal compound is oriented and the oriented state is fixed (hereinafter referred to as a liquid crystal film). Since the birefringence (Δn) of a liquid crystal compound is significantly larger than that of a resin, the thickness of the liquid crystal film to obtain a desired in-plane retardation can be made significantly smaller than that of a stretched film of a resin film. A liquid crystal film is typically formed by applying a composition including a liquid crystal compound to an alignment substrate and solidifying or curing the applied film. The liquid crystal film thus formed is laminated to a polarizing plate, and then the alignment substrate is peeled off. However, when the liquid crystal film is used for a thin polarizing plate, peeling failure may occur when peeling off the alignment substrate. Specifically, when peeling off the alignment substrate, the liquid crystal film may also be peeled off together. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-222282 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been made to solve the above-described conventional problems, and its main object is to provide an optical laminate including a liquid crystal alignment cured layer and suppressing peeling defects when peeling an alignment substrate.
Means for Solving the Problems
[0005] [1] The optical laminate according to an embodiment of the present invention includes a polarizing plate including a polarizer, a retardation layer laminated on the polarizing plate via a first adhesive layer, and a substrate detachably laminated on the retardation layer; the retardation layer includes, in order from the polarizing plate side, a first liquid crystal alignment cured layer and a second liquid crystal alignment cured layer laminated on the first liquid crystal alignment cured layer via a second adhesive layer; the retardation layer has a circular polarization function or an elliptical polarization function as a whole, has a relationship of Re(450) < Re(550) < Re(650), and has an Nz coefficient of 0.30 to 0.70; the substrate is an alignment substrate of the second liquid crystal alignment cured layer, and its tensile elastic modulus is 3000 N / mm 2 or more. [2] In the above [1], the thickness of the substrate is 75 μm or more. [3] In the above [1] or [2], the substrate is a single film. [4] In the above [1] or [2], the substrate has a laminated structure of two or more layers. [5] In any one of the above [1] to [4], the polarizing plate includes protective layers disposed on both sides of the polarizer, and the thickness of the polarizing plate is 100 μm or less. [6] In any one of the above [1] to [5], the total thickness from the polarizing plate to the second liquid crystal alignment cured layer is 110 μm or less. [7] In any one of the above [1] to [6], the first adhesive layer is composed of an ultraviolet curable adhesive.
Effects of the Invention
[0006] According to an embodiment of the present invention, it is possible to realize an optical laminate including a liquid crystal alignment cured layer and suppressing peeling defects when peeling an alignment substrate.
Brief Description of the Drawings
[0007] [Figure 1] 1 is a schematic cross-sectional view of an optical laminate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Representative embodiments of the present invention will be described below, but the present invention is not limited to these embodiments.
[0009] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation of a film measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation of a film measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re=(nx-ny)×d, where d(nm) is the thickness of the film. (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction of a film measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction of a film measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth=(nx-nz)×d, where d(nm) is the thickness of the film. (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, unless otherwise specified, the angles include angles in both clockwise and counterclockwise directions.
[0010] A. Optical laminate FIG. 1 is a schematic cross-sectional view of an optical laminate according to one embodiment of the present invention. The optical laminate 100 in the illustrated example has a polarizing plate 10, a retardation layer 20 laminated on the polarizing plate 10 via a first adhesive layer 30, and a substrate 40 laminated on the retardation layer 20 in a peelable manner. The polarizing plate 10 typically includes a polarizer 11 and protective layers 12 and 13 disposed on both sides of the polarizer 11. Depending on the purpose, at least one of the protective layers 12 and 13 may be omitted. Therefore, the polarizing plate may be a so-called double-protection polarizing plate, a so-called single-protection polarizing plate, or may be composed of only a polarizer. The polarizing plate is preferably a double-protection polarizing plate, and the thickness of the polarizing plate is, for example, 110 μm or less, preferably 100 μm or less, and more preferably 15 μm to 100 μm. By configuring the polarizing plate with double protection and setting its thickness to a specific value or less, the effects according to the embodiments of the present invention can be remarkable.
[0011] The retardation layer 20 includes, in order from the polarizing plate 10 side, a first liquid crystal alignment cured layer 21 and a second liquid crystal alignment cured layer 22 laminated on the first liquid crystal alignment cured layer 21 via a second adhesive layer 25. By using the liquid crystal alignment cured layer as the retardation layer, a desired in-plane retardation can be realized with a thickness significantly thinner than that of a stretched film of a resin film. As a result, the optical laminate can be significantly thinned. The retardation layer 20 as a whole (as a laminate of the first liquid crystal alignment cured layer 21 and the second liquid crystal alignment cured layer 22) has a circular polarization function or an elliptical polarization function, has a relationship of Re(450) < Re(550) < Re(650), and its Nz coefficient is 0.30 to 0.70. According to the embodiment of the present invention, in an optical laminate having such a specific retardation layer, peeling failure can be suppressed when the substrate is peeled off. In this specification, the "liquid crystal alignment cured layer" refers to a layer in which a liquid crystal compound is aligned in a predetermined direction within the layer and the alignment state is fixed. The "liquid crystal alignment cured layer" is a concept including an alignment cured layer obtained by curing a liquid crystal monomer.
[0012] The substrate 40 is an alignment substrate for the second liquid crystal alignment solidified layer 22. That is, a liquid crystal composition for forming the second liquid crystal alignment solidified layer is applied to the substrate 40, and the liquid crystal compound in the composition is aligned by the alignment regulating force of the substrate 40, and the liquid crystal compound is solidified or cured in the aligned state to form the second liquid crystal alignment solidified layer 22. A laminate of the substrate 40 and the second liquid crystal alignment solidified layer 22 is laminated on a polarizing plate (in the illustrated example, the first liquid crystal alignment solidified layer 21 laminated on the polarizing plate 10). The substrate 40 can be typically peeled off and removed when preparing an optical laminate as a final product. That is, the substrate 40 is peelably laminated on the second liquid crystal alignment solidified layer 22. In the embodiment of the present invention, the tensile modulus of the substrate 40 is 3000 N / mm 2 That is all. With this configuration, peeling failure when peeling off the substrate can be suppressed. Specifically, peeling off of the second liquid crystal alignment solidified layer together with the substrate can be prevented or effectively suppressed. The first liquid crystal alignment solidified layer 21 is also formed in the same manner as above and laminated on the polarizing plate, and it is preferable that the alignment substrate of the first liquid crystal alignment solidified layer 21 is also made of the same substrate as the substrate 40.
[0013] In the optical laminate, the total thickness from the polarizing plate to the second liquid crystal alignment solidified layer (i.e., the portion that can become the final product) is, for example, 120 μm or less, preferably 110 μm or less, and more preferably 20 μm to 110 μm. In such a very thin optical laminate, peeling failure when peeling off the substrate is significant, but according to the embodiment of the present invention, such peeling failure can be suppressed.
[0014] The components of the optical laminate will be specifically described below.
[0015] B. Polarizing plate B-1.Polarizer The polarizer 11 is typically made of a polyvinyl alcohol (PVA) resin film containing a dichroic material (e.g., iodine). Examples of PVA resins include polyvinyl alcohol, partially formalized polyvinyl alcohol, ethylene-vinyl alcohol copolymer, and partially saponified ethylene-vinyl acetate copolymer.
[0016] The PVA-based resin preferably contains an acetoacetyl-modified PVA-based resin. With this configuration, a polarizer having desired mechanical strength can be obtained. The amount of the acetoacetyl-modified PVA-based resin is preferably 5% by weight to 20% by weight, and more preferably 8% by weight to 12% by weight, based on 100% by weight of the entire PVA-based resin. If the amount is within this range, a polarizer having better mechanical strength can be obtained.
[0017] The polarizer preferably contains iodide or sodium chloride (sometimes collectively referred to as halide). Examples of iodide include potassium iodide, sodium iodide, and lithium iodide. The content of the halide in the polarizer is preferably 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, based on 100 parts by weight of the PVA-based resin. In the manufacturing method described below, the halide can be blended in a coating liquid that forms a PVA-based resin layer, which is a precursor of the polarizer, and finally introduced into the polarizer. By introducing a halide into the polarizer, the orientation of the PVA molecules in the polarizer can be increased, and therefore a polarizer having excellent optical properties (typically, both a high polarization degree and a high single transmittance) can be realized.
[0018] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is preferably 41.0% to 46.0%, and more preferably 42.0% to 45.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more. According to the embodiment of the present invention, even if the single transmittance is in the above range, the degree of polarization can be maintained in such a range.
[0019] The thickness of the polarizer is, for example, 12 μm or less, preferably 10 μm or less, more preferably 1 μm to 8 μm, and further preferably 3 μm to 7 μm. By combining such a thin polarizer with a liquid crystal alignment solidified layer, it is possible to significantly reduce the thickness of the optical laminate. Furthermore, if the thickness of the polarizer is within the above range, curling during heating can be well suppressed, and good appearance durability during heating can be obtained.
[0020] The polarizer can be produced by any appropriate method. For example, the resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.
[0021] Specific examples of polarizers made of a single-layer resin film include hydrophilic polymer films such as PVA films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films that have been dyed with iodine or a dichroic substance such as a dichroic dye and stretched, and polyene-based oriented films such as dehydrated PVA films and dehydrochlorinated polyvinyl chloride films. A polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it is preferably used because of its excellent optical properties.
[0022] The dyeing with iodine is carried out, for example, by immersing the PVA-based film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment, or may be carried out while dyeing. Alternatively, the film may be stretched and then dyed. If necessary, the PVA-based film may be subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like. For example, by immersing the PVA-based film in water and washing it with water before dyeing, it is possible to wash off dirt and antiblocking agents on the surface of the PVA-based film, and also to swell the PVA-based film and prevent uneven dyeing.
[0023] Specific examples of polarizers obtained using a laminate include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, the laminate is preferably subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of the PVA, and to achieve high optical properties. In addition, by simultaneously increasing the orientation of the PVA in advance, problems such as a decrease in the orientation of the PVA or dissolution when immersed in water in the subsequent dyeing and stretching steps can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation of the polyvinyl alcohol molecules can be disturbed and the orientation can be reduced, compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of a polarizer obtained by immersing the laminate in a liquid through a treatment process such as a dyeing treatment and an underwater stretching treatment. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction through a drying shrinkage treatment.The obtained resin substrate / polarizer laminate may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or any suitable protective layer may be laminated on the peeled surface of the resin substrate / polarizer laminate after peeling the resin substrate from the resin substrate / polarizer laminate, or on the surface opposite to the peeled surface, depending on the purpose. Details of the method for producing such a polarizer are described in, for example, JP2012-73580A and JP6470455A. The entire disclosures of these publications are incorporated herein by reference.
[0024] B-2.Protective layer The protective layers 12 and 13 are made of any suitable resin film. Representative materials for the resin film include cellulose resins such as triacetyl cellulose (TAC), cycloolefin resins such as polynorbornene, (meth)acrylic resins, polyester resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polyolefin resins such as polyethylene, and polycarbonate resins. Representative examples of (meth)acrylic resins include (meth)acrylic resins having a lactone ring structure. (Meth)acrylic resins having a lactone ring structure are described in, for example, JP-A-2000-230016, JP-A-2001-151814, JP-A-2002-120326, JP-A-2002-254544, and JP-A-2005-146084. These publications are incorporated herein by reference. From the viewpoint of ease of processing into irregular shapes, a cellulose-based resin is preferred, and TAC is more preferred. From the viewpoint of obtaining a polarizing plate having low moisture permeability and excellent durability, a cycloolefin-based resin and a (meth)acrylic resin are preferred.
[0025] The optical laminate is typically placed on the viewing side of an image display device, and the protective layer 12 is typically placed on the viewing side. Therefore, the protective layer 12 may be subjected to a surface treatment as necessary. Examples of the surface treatment include hard coat treatment, anti-reflection treatment, anti-sticking treatment, and anti-glare treatment. Furthermore, the protective layer 12 may be subjected to a treatment for improving visibility when viewed through polarized sunglasses (typically, imparting an (elliptical) polarization function or imparting an ultra-high phase difference) as necessary. By performing such treatment, excellent visibility can be achieved even when the display screen is viewed through polarized lenses such as polarized sunglasses. Therefore, the optical laminate can be suitably applied to image display devices that can be used outdoors.
[0026] In one embodiment, the protective layer 13 is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the retardation in the thickness direction Rth(550) is -10 nm to +10 nm.
[0027] The thickness of each of the protective layers 12 and 13 is preferably 10 μm to 80 μm, more preferably 12 μm to 40 μm, and further preferably 15 μm to 35 μm. When the protective layer 12 is surface-treated, the thickness of the protective layer 12 includes the thickness of the surface treatment layer.
[0028] C. Retardation layer As described above, the retardation layer 20 includes a first liquid crystal alignment cured layer 21 and a second liquid crystal alignment cured layer 22 in order from the polarizer side. Further, as described above, the retardation layer 20 as a whole (as a laminate of the first liquid crystal alignment cured layer 21 and the second liquid crystal alignment cured layer 22) has a circular polarization function or an elliptical polarization function, has a relationship of Re(450) < Re(550) < Re(650), and its Nz coefficient is 0.30 to 0.70. Regarding the description of the retardation layer in this section, simply referring to the "retardation layer" means explaining it as a whole, and simply referring to the "liquid crystal alignment cured layer" means explaining the first liquid crystal alignment cured layer and the second liquid crystal alignment cured layer together.
[0029] For the retardation layer 20, Re(550) is preferably 100 nm to 200 nm, more preferably 120 nm to 190 nm, still more preferably 130 nm to 180 nm, and particularly preferably 150 nm to 170 nm. If the Re(550) of the retardation layer is within such a range, the retardation layer can exhibit a good circular polarization function or elliptical polarization function in combination with a polarizer.
[0030] The Nz coefficient of the retardation layer 20 is 0.30 to 0.70 as described above. Therefore, the retardation layer 20 exhibits a refractive index characteristic of nx > nz > ny. With such a configuration, reflection in an oblique direction can be preferably prevented, and a wide viewing angle of the antireflection function can be achieved. The Nz coefficient is preferably 0.35 to 0.65, more preferably 0.40 to 0.60, and still more preferably 0.45 to 0.55.
[0031] The retardation layer 20 has a relationship of Re(450) < Re(550) < Re(650). That is, the retardation layer 20 preferably exhibits an inverse-dispersion wavelength dependence in which the retardation value increases with the wavelength of the measurement light. With such a configuration, a good antireflection function can be realized in a very wide wavelength band. Re(450) / Re(550) is, for example, greater than 0.5 and less than 1.0, preferably 0.7 to 0.95, more preferably 0.75 to 0.92, and even more preferably 0.8 to 0.9. Re(650) / Re(550) is preferably 1.0 or more and less than 1.15, more preferably 1.03 to 1.1.
[0032] Examples of the liquid crystal compound used for the liquid crystal alignment curing layer include liquid crystal polymers and liquid crystal monomers. The liquid crystal compound is preferably polymerizable (i.e., a liquid crystal monomer). When the liquid crystal compound is polymerizable, the alignment state of the liquid crystal compound can be fixed by polymerizing it after aligning the liquid crystal compound. Here, the polymer formed by polymerization is non-liquid crystalline. Therefore, in the formed liquid crystal alignment curing layer, for example, a transition to a liquid crystal phase, a glass phase, or a crystal phase due to a temperature change peculiar to the liquid crystal compound does not occur. As a result, the liquid crystal alignment curing layer becomes a retardation layer that is not affected by temperature changes and has extremely excellent stability.
[0033] In one embodiment, the liquid crystal alignment solidified layer may be formed using a composition containing a polymerizable liquid crystal compound (polymerizable liquid crystal compound, i.e., liquid crystal monomer). In this specification, the polymerizable liquid crystal compound contained in the composition refers to a compound having a polymerizable group and liquid crystal properties. The polymerizable group means a group involved in a polymerization reaction, and is preferably a photopolymerizable group. Here, the photopolymerizable group refers to a group that can be involved in a polymerization reaction by an active radical or acid generated from a photopolymerization initiator. As the liquid crystal monomer, for example, polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445, etc., can be used. Specific examples of such polymerizable mesogenic compounds include LC242 (trade name) from BASF, E7 (trade name) from Merck, and LC-Sillicon-CC3767 (trade name) from Wacker-Chem.
[0034] The mechanism by which the liquid crystal compound exhibits liquid crystallinity may be thermotropic or lyotropic. The liquid crystal phase may be nematic or smectic. From the viewpoint of ease of production, the liquid crystallinity is preferably thermotropic nematic liquid crystal.
[0035] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on the type of the liquid crystal monomer. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.
[0036] The birefringence Δn of the liquid crystal alignment solidified layer is preferably 0.06 or more, more preferably 0.08 or more, even more preferably 0.09 or more, and particularly preferably 0.10 or more. The upper limit of Δn may be, for example, 0.13, or may be, for example, 0.12. If Δn is in such a range, a desired in-plane retardation can be realized with a very thin thickness. As a result, it becomes possible to further thin the liquid crystal alignment solidified layer and the optical laminate, which can ultimately contribute to a significant thinning of the image display device.
[0037] The liquid crystal alignment solidified layer may exhibit an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light, may exhibit a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or may exhibit a flat wavelength dispersion characteristic in which the retardation value changes very little depending on the wavelength of the measurement light.
[0038] The first liquid crystal alignment solidified layer 21 can typically function as a λ / 2 plate, and the second liquid crystal alignment solidified layer 22 can typically function as a λ / 4 plate. Specifically, the Re(550) of the first liquid crystal alignment solidified layer is preferably 200 nm to 300 nm, more preferably 230 nm to 290 nm, and even more preferably 250 nm to 280 nm; the Re(550) of the second liquid crystal alignment solidified layer is preferably 100 nm to 200 nm, more preferably 120 nm to 170 nm, and even more preferably 130 nm to 150 nm. The thickness of the first liquid crystal alignment solidified layer can be adjusted so that a desired in-plane retardation of the λ / 2 plate is obtained. Specifically, the thickness can be, for example, 2.0 μm to 4.0 μm. The thickness of the second liquid crystal alignment solidified layer can be adjusted so that a desired in-plane retardation of the λ / 4 plate is obtained. Specifically, the thickness can be, for example, 1.0 μm to 2.5 μm. The angle between the slow axis of the first liquid crystal alignment solidified layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and even more preferably 14° to 16°; the angle between the slow axis of the second liquid crystal alignment solidified layer and the absorption axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and even more preferably 74° to 76°. The arrangement order of the first liquid crystal alignment solidified layer and the second liquid crystal alignment solidified layer may be reversed, and the angle between the slow axis of the first liquid crystal alignment solidified layer and the absorption axis of the polarizer and the angle between the slow axis of the second liquid crystal alignment solidified layer and the absorption axis of the polarizer may be reversed.
[0039] A side-chain type thermotropic liquid crystal polymer may be introduced into the first liquid crystal alignment solidified layer and / or the second liquid crystal alignment solidified layer (substantially the liquid crystal composition forming these). The introduction of a side-chain type thermotropic liquid crystal polymer can act to homeotropically align (vertically align) the liquid crystal monomer. As a result, the nz of the first liquid crystal alignment solidified layer and / or the second liquid crystal alignment solidified layer can be increased, and as a result, the Nz coefficient of the first liquid crystal alignment solidified layer and / or the second liquid crystal alignment solidified layer can be set to the desired range. Finally, the Nz coefficient of the retardation layer can be set to the desired range without providing a positive C plate described later.
[0040] As the side-chain type thermotropic liquid crystal polymer, typically, a copolymer having a monomer unit containing a thermotropic liquid crystal fragment side chain and a monomer unit containing a non-liquid crystal fragment side chain is used. When the polymer has a thermotropic liquid crystal fragment in the side chain, the side-chain type liquid crystal polymer can be aligned when the liquid crystal composition is heated to a predetermined temperature. When the side-chain type polymer has a non-liquid crystal fragment in the side chain, the non-liquid crystal fragment can interact with the photopolymerizable liquid crystal monomer to homeotropically align the photopolymerizable liquid crystal monomer.
[0041] As the side-chain type thermotropic liquid crystal polymer, a copolymer having a liquid crystal monomer unit represented by general formula (I) and a non-liquid crystal monomer unit represented by general formula (II) is preferably used. [ka] [ka]
[0042] In formula (I), R 1 is a hydrogen atom or a methyl group, and R 2 is a cyano group, a fluoro group, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms; X 1 is -CO2- or -OCO-. a is an integer of 1 to 6, and b and c are each independently 1 or 2.
[0043] In formula (II), R 3 is a hydrogen atom or a methyl group, and R 4 is an alkyl group having 7 to 22 carbon atoms, a fluoroalkyl group having 1 to 22 carbon atoms, or a group represented by the following general formula (III). [ka]
[0044] In formula (III), R 5 is an alkyl group having 1 to 5 carbon atoms, and d is an integer of 1 to 6.
[0045] The ratio of the liquid crystal monomer unit and the non-liquid crystal monomer unit in the side chain type liquid crystal monomer can be appropriately set according to the purpose. The ratio (molar ratio) of the non-liquid crystal monomer to the total of the liquid crystal monomer unit and the non-liquid crystal monomer unit is preferably 0.05 to 0.8, more preferably 0.1 to 0.6, and further preferably 0.15 to 0.5. With such a configuration, a liquid crystal alignment solidified layer exhibiting a desired refractive index characteristic (Nz coefficient) can be obtained.
[0046] The ratio of the liquid crystal monomer to the side-chain liquid crystal polymer in the liquid crystal composition can be appropriately set depending on the purpose. When the content of the side-chain liquid crystal polymer is high, the Nz coefficient tends to be small; when the content of the liquid crystal monomer is high, the Nz coefficient tends to be small. The content of the liquid crystal monomer is preferably 1.2 to 20 times, more preferably 1.3 to 10 times, further preferably 1.4 to 9 times, and particularly preferably 1.5 to 8 times, the content of the side-chain liquid crystal polymer. With such a configuration, a liquid crystal alignment solidified layer exhibiting a desired refractive index characteristic (Nz coefficient) can be obtained.
[0047] Details of the side-chain liquid crystal polymer and the method for forming a liquid crystal alignment solidified layer having an Nz coefficient of less than 1.0 are described in Japanese Patent No. 6769921, the disclosure of which is incorporated herein by reference.
[0048] The retardation layer 20 may further include a positive C plate. The positive C plate has a refractive index characteristic of nz>nx=ny. The thickness direction retardation Rth(550) of the positive C plate is preferably -50 nm to -300 nm, more preferably -70 nm to -250 nm, further preferably -90 nm to -200 nm, and particularly preferably -100 nm to -180 nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane retardation Re(550) of the positive C plate may be less than 10 nm.
[0049] The positive C plate can be formed, for example, using a composition containing the above-mentioned side-chain liquid crystal polymer. Specific examples of the method for forming the positive C plate include the methods described in
[0020] to
[0028] of JP 2002-333642 A. In this case, the thickness of the positive C plate is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and even more preferably 0.5 μm to 5 μm.
[0050] D. Base material The tensile modulus of the substrate 40 is 3000 N / mm 2 That is all. With this configuration, peeling failure when peeling off the substrate can be suppressed. Specifically, peeling off of the second liquid crystal alignment solidified layer together with the substrate can be prevented or effectively suppressed. The tensile modulus of the substrate is preferably 4000 N / mm 2 More preferably, it is 5000N / mm 2 More preferably, it is 6000N / mm 2 More preferably, it is 6500N / mm 2 On the other hand, the tensile modulus of the substrate is, for example, 9000 N / mm 2 It may be less than or equal to 8500 N / mm 2 The tensile modulus can be determined in accordance with JIS K 7161.
[0051] The peeling force of the substrate 40 is preferably 1.2 N / 50 mm or less, more preferably 1.0 N / 50 mm or less, even more preferably 0.8 N / 50 mm or less, and particularly preferably 0.7 N / 50 mm or less. On the other hand, the peeling force of the substrate can be, for example, 0.1 N / 50 mm or more, and can be, for example, 0.2 N / 50 mm or more. With such a configuration, peeling failure when peeling the substrate can be suppressed, similarly to the case where the tensile modulus is set to a predetermined value or more. Specifically, peeling of the second liquid crystal alignment solidified layer together with the substrate can be prevented or effectively suppressed.
[0052] As described above, the substrate is the alignment substrate of the second liquid crystal alignment solidified layer, and therefore has an alignment regulating force. The alignment regulating force can be typically imparted by rubbing alignment, stretching substrate alignment, or photo-alignment. Preferably, it is stretching substrate alignment or photo-alignment.
[0053] The substrate may have any suitable structure as long as the desired tensile modulus is obtained. Specifically, the substrate may be a single film, or may have a laminated structure of two or more layers (may be a laminate). The substrate is typically composed of a resin film. Therefore, the substrate may be a single resin film, or may be a laminate including a first resin film and a second resin film. A single film may be excellent in cost and versatility. When a single film cannot achieve both a desired orientation restricting force and a desired tensile modulus, a laminate can achieve both by complementing these properties with a plurality of resin films. The laminate may be a three-layer laminate further including a third resin film, a four-layer laminate further including a fourth resin film, or a laminate of five or more layers. Each resin film included in the laminate is typically laminated via a pressure-sensitive adhesive layer. The laminate preferably has a structure of a first resin film / pressure-sensitive adhesive layer / second resin film having an orientation restricting force.
[0054] Representative materials constituting the resin film include cellulose resins such as TAC, cycloolefin resins such as polynorbornene, (meth)acrylic resins, polyester resins such as PET and PEN, polyolefin resins such as polyethylene and polypropylene, and polycarbonate resins.Specific configurations of the substrate preferably include a single film of a TAC film having an orientation control force, and a laminate having a configuration of a TAC film having an orientation control force / adhesive layer / PET film.
[0055] The thickness of the substrate may vary depending on the material of the substrate, the structure of the substrate, etc. The thickness of the substrate may be, for example, 75 μm or more, or, for example, 77 μm or more, or, for example, 80 μm or more, or, for example, 85 μm or more, or, for example, 88 μm or more. On the other hand, the thickness of the substrate may be, for example, 120 μm or less, or, for example, 110 μm or less, or, for example, 100 μm or less.
[0056] E. 1st adhesive layer A representative example of an adhesive that can constitute the first adhesive layer 30 is an active energy ray curable adhesive. By using an active energy ray curable adhesive as the first adhesive layer, the first adhesive layer can be thinned, and as a result, an optical laminate with excellent flexibility can be obtained. Furthermore, the first adhesive layer can be made high in refractive index, and the difference in refractive index with the adjacent first liquid crystal alignment solidified layer can be reduced. As a result, reflection at the interface between the first adhesive layer and the first liquid crystal alignment solidified layer is suppressed, and an optical laminate with excellent anti-reflection performance can be obtained. The active energy ray curable adhesive can be selected from radical curable, cationic curable, anionic curable, and the like as needed, and can be used in appropriate combination, such as a hybrid of radical curable and cationic curable. The radical curable adhesive can be, for example, an adhesive containing a compound (e.g., a monomer and / or oligomer) having a radical polymerizable group such as a (meth)acrylate group or a (meth)acrylamide group as a curing component. As for the active energy ray curable adhesive, the type, combination, and compounding ratio of the double bond-containing monomer and / or oligomer, crosslinking agent, etc. can be adjusted to obtain an active energy ray curable adhesive having desired properties (e.g., storage modulus after curing). Examples of the active energy ray include ultraviolet light, visible light, infrared light, and electron beams. The ultraviolet ray curable adhesive is preferred because it has excellent versatility and ease of handling. Note that the active energy ray curable adhesive is well known in the industry, so a detailed description of the composition is omitted.
[0057] The thickness of the first adhesive layer is preferably 0.1 μm to 3.0 μm, more preferably 0.5 μm to 2.0 μm, and further preferably 0.8 μm to 1.5 μm. Such a thickness can contribute to making the optical laminate thinner.
[0058] F.Second adhesive layer The second adhesive layer 25 may be made of any appropriate adhesive. The thickness of the second adhesive layer is preferably 0.1 μm to 3.0 μm, more preferably 0.5 μm to 2.0 μm, and even more preferably 0.8 μm to 1.5 μm. Such a thickness can contribute to a thinner optical laminate, similar to the first adhesive layer. EXAMPLES
[0059] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Measurement methods and evaluation methods in the examples are as follows.
[0060] (1) In-plane retardation Re(550), thickness retardation Rth(550) and Nz coefficient Re(550) and Rth(550) were measured using an "AXO-Scan" manufactured by AXOMETRICS. The Nz coefficient was calculated from Rth / Re.
[0061] (2) Tensile modulus The substrates used in the examples and comparative examples were subjected to a tensile test in accordance with JIS K 7161 to determine the tensile modulus of elasticity.
[0062] (3) Peeling strength Measurements were performed according to JIS Z 0237. Specifically, the optical laminates obtained in the examples and comparative examples were cut into a length of 150 mm and a width of 50 mm to prepare measurement samples. Using a tensile tester (manufactured by Tester Sangyo Co., Ltd., product name "TE-702 high-speed peel tester"), the peel force was measured when the substrate of the measurement sample was peeled off at a peel angle of 90° and a peel speed of 15,000 mm / min.
[0063] (4) Peeling evaluation The optical laminates obtained in the Examples and Comparative Examples were transported by rolls, and the substrate was peeled from the optical laminate, and the presence or absence of peeling defects was observed. The results were evaluated according to the following criteria. Good: Only the base material was peeled off well. Defective: The second liquid crystal alignment layer peeled off together with the substrate.
[0064] [Example 1] 1. Preparation of Polarizing Plates 1-1. Preparation of polarizer As a thermoplastic resin substrate, a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched 2.4 times in the machine direction (longitudinal direction) in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the finally obtained polarizer would be the desired value (dyeing treatment). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, the film was dried in an oven maintained at about 90° C. while being brought into contact with a SUS heated roll whose surface temperature was maintained at about 75° C. (drying shrinkage treatment). In this manner, a polarizer having a thickness of about 5 μm was formed on the resin substrate, and a polarizing plate having a resin substrate / polarizer structure was obtained. The single transmittance Ts of the polarizer was 43.3%.
[0065] 1-2. Preparation of polarizing plate An HC-TAC film was attached to the surface of the obtained polarizer (the surface opposite to the resin substrate) via a UV-curable adhesive. The HC-TAC film was a film in which an HC layer (7 μm thick) was formed on a triacetyl cellulose (TAC) film (25 μm thick), and the TAC film was attached to the polarizer side. Next, the resin substrate was peeled off, and a TAC film (25 μm thick) was attached to the peeled surface via a UV-curable adhesive. In this way, a polarizing plate having a structure of HC layer / TAC film (protective layer) / polarizer / TAC film (protective layer) was obtained.
[0066] 2. Preparation of retardation layer A photopolymerizable liquid crystal compound exhibiting a nematic liquid crystal phase (BASF's "Paliocolor LC242", chemical formula below) was dissolved in cyclopentanone to prepare a solution with a solids concentration of 20% by weight. A leveling agent (DIC's "Megafac F-563"), a photopolymerization initiator (IGM Resins' "Omnirad907") and a crosslinking agent (Shin-Nakamura Chemical Co., Ltd.'s "A-DCP") were added to this solution to prepare a coating liquid for forming a liquid crystal alignment solidified layer. A TAC film (thickness: 80 μm, tensile modulus: 3391 N / mm 2 The above-mentioned liquid crystal alignment solidified layer forming coating solution was applied onto this substrate using a spin coater, and the substrate was heated at 100°C for 3 minutes to align the liquid crystal compound. After cooling to room temperature, the substrate was exposed to an integrated light dose of 600 mJ / cm2 in a nitrogen atmosphere. 2The layer was irradiated with ultraviolet light of 1000 nm to perform photocuring, and the alignment state of the liquid crystal compound was fixed. In this way, a laminate of the substrate / first liquid crystal alignment solidified layer (thickness: 2 μm, Re(550): 270 nm) was obtained. A laminate of the substrate / second liquid crystal alignment solidified layer (thickness: 1 μm, Re(550): 140 nm) was obtained in the same manner as above, except that the coating thickness was changed. [ka]
[0067] 3. Preparation of Positive C Plates A liquid crystal coating solution was prepared by dissolving 20 parts by weight of a side-chain liquid crystal polymer having a weight average molecular weight of 5000 and the following chemical formula (n=0.35, and shown as a block polymer for convenience), 80 parts by weight of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: trade name Paliocolor LC242), and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: trade name Irgacure 907) in 200 parts by weight of cyclopentanone. The coating solution was then applied to a PET substrate that had been subjected to a vertical alignment treatment using a bar coater, and the liquid crystal was aligned by heating and drying at 80°C for 4 minutes. The liquid crystal layer was irradiated with ultraviolet light to harden the liquid crystal layer, forming a positive C plate (thickness 3 μm) on the substrate. [ka]
[0068] 4. Preparation of Optical Laminate A first liquid crystal alignment solidified layer was attached to the TAC film surface opposite to the HC layer of the polarizing plate via a UV-curable adhesive (thickness 1 μm), and then the substrate was peeled off. Next, a positive C plate was transferred to the surface of the first liquid crystal alignment solidified layer via a UV-curable adhesive (thickness 1 μm). Furthermore, a second liquid crystal alignment solidified layer was attached to the surface of the positive C plate via a UV-curable adhesive (thickness 1 μm) to obtain an optical laminate having a polarizing plate / retardation layer / substrate configuration. The Re(550) of the entire retardation layer was 168 nm, and the Nz coefficient was 0.52. The peeling force and the presence or absence of peeling failure when peeling the substrate from the obtained optical laminate were evaluated. The results are shown in Table 1.
[0069] [Example 2] As the substrate, another TAC film (thickness: 80 μm, tensile modulus: 8147 N / mm 2 An optical laminate was produced in the same manner as in Example 1, except that ) was used. The obtained optical laminate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0070] [Example 3] An optical laminate was produced in the same manner as in Example 1, except that a laminate of TAC film (thickness: 40 μm) / adhesive layer (thickness: 10 μm) / PET film (thickness: 38 μm) was used as the substrate. The substrate was produced by laminating a surface protection film (product name "RP1010M") manufactured by Nitto Denko Corporation to the TAC film. The tensile modulus of the substrate was 7143 N / mm 2 The obtained optical layered body was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0071] [Example 4] An optical laminate was produced in the same manner as in Example 1, except that a laminate of TAC film (thickness: 40 μm) / adhesive layer (thickness: 10 μm) / PET film (thickness: 38 μm) was used as the substrate. The substrate was produced by laminating a surface protection film (product name "RP109F") manufactured by Nitto Denko Corporation to the TAC film. The tensile modulus of the substrate was 6901 N / mm 2 The obtained optical layered body was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0072] [Example 5] An optical laminate was produced in the same manner as in Example 1, except that a laminate of TAC film (thickness: 40 μm) / adhesive layer (thickness: 5 μm) / PET film (thickness: 38 μm) was used as the substrate. The substrate was produced by laminating a surface protection film (product name "HP300") manufactured by Nitto Denko Corporation to a TAC film. The tensile modulus of the substrate was 4079 N / mm 2 The obtained optical layered body was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0073] [Comparative Example 1] Another TAC film (thickness: 40 μm, tensile modulus: 2021 N / mm 2 An optical laminate was produced in the same manner as in Example 1, except that ) was used. The obtained optical laminate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0074] [Comparative Example 2] An optical laminate was produced in the same manner as in Example 1, except that a laminate of a TAC film (thickness: 40 μm) / polyethylene film (thickness: 32 μm) was used as the substrate. The substrate was produced by laminating a self-adhesive surface protection film (product name "Tretec") manufactured by Toray Industries, Inc. to the TAC film. The tensile modulus of the substrate was 2376 N / mm 2 The obtained optical layered body was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0075] [Table 1] [Industrial Applicability]
[0076] The optical laminate according to the embodiment of the present invention can be suitably used in image display devices (typically, liquid crystal display devices and organic EL display devices). [Explanation of symbols]
[0077] 10 Polarizing plate 11 Polarizer 12 Protective layer 13 Protective layer 20 Retardation layer 21 First liquid crystal alignment solidification layer 22 Second liquid crystal alignment solidification layer 40 Base material 100 Optical laminate
Claims
1. A polarizing plate including a polarizer, a retardation layer laminated on the polarizing plate via a first adhesive layer, and a base material peelably laminated on the retardation layer, the retardation layer includes, in order from the polarizing plate side, a first liquid crystal alignment solidified layer and a second liquid crystal alignment solidified layer laminated on the first liquid crystal alignment solidified layer via a second adhesive layer; the retardation layer as a whole has a circular polarization function or an elliptically polarizing function, has a relationship of Re(450)<Re(550)<Re(650), and has an Nz coefficient of 0.30 to 0.70; The substrate is an alignment substrate for the second liquid crystal alignment solidified layer, and has a tensile modulus of 3000 N / mm 2 That's all. Optical laminate.
2. The optical laminate according to claim 1 , wherein the substrate has a thickness of 75 μm or more.
3. The optical laminate according to claim 2 , wherein the substrate is a single film.
4. The optical laminate according to claim 2 , wherein the substrate has a laminated structure of two or more layers.
5. 5. The optical laminate according to claim 1, wherein the polarizing plate includes protective layers disposed on both sides of the polarizer, and the polarizing plate has a thickness of 100 μm or less.
6. 5. The optical laminate according to claim 1, wherein a total thickness from the polarizing plate to the second liquid crystal alignment solidified layer is 110 μm or less.
7. The optical laminate according to claim 1 , wherein the first adhesive layer is made of an ultraviolet-curable adhesive.
Citation Information
Patent Citations
Optical film, image display device, transfer body for optical film, manufacturing method of optical film, and manufacturing method of transfer body for optical film
JP2015040905A
Optical film, transfer film, image display device, method for manufacturing optical film, and method for manufacturing transfer film
JP2016206217A
Manufacturing method of thin circular polarization plate
JP2021018354A
Polarization plate with retardation layer and image display device
JP2022037502A
Optical film with adhesive layer and image display device including optical film with adhesive layer
JP2022092281A